210Po and 210Pb in forest mushrooms of genus Leccinum and topsoil from northern Poland and its contribution to the radiation dose. (December 2018) - Szymańska, Karolina; Falandysz, Jerzy; Skwarzec, Bogdan; Strumińska-Parulska, Dagmara
Abstract: Wild growing mushrooms are traditional food items for man and also an important source of nutrients for small and big wildlife. Nevertheless, they can be species - specifically vulnerable for contamination with heavy metals and radionuclides. We studied a less known phenomenon of accumulation of highly toxic, the alpha-radiation emitter such as 210 Po and the beta emitter 210 Pb by three Leccinum mushrooms: orange oak bolete L. aurantiacum (Bull.) Gray (previous name Leccinum aurantiacum var. quercinum Pilát), foxy bolete L. vulpinum Watling and slate bolete L. duriusculum (Schulzer ex Kalchbr.) Singer. Fungal and soil materials were collected from areas of a different geochemical composition in the northern regions of Poland. In parallel evaluated was the risk to human consumer due to possible intake of 210 Po and 210 Pb with a mushroom meal. Results showed a heterogeneous distribution of 210 Po and 210 Pb activity concentrations within caps and stipes of fruiting bodies. Overall activity concentration for whole dried fungi material ranged from 0.59 ± 0.38 to 3.2 ± 0.2 Bq 210 Po kg −1 and from 0.45 ± 0.04 to 3.1 ± 0.2 Bq 210 Pb kg −1 . Evaluation showed that Leccinum mushrooms consumed by locals in typical quantity of 0.5 kg (dry biomass) can contribute into annual effective radiation dose at 0.90–3.81 μSv from 210 Po decay and 0.31–2.14 μSv from 210 Pb decay, which is a small portion of the annual effective radiation dose of 210 Po and 210 Pb for human inhabiting the northern regions of Poland. Highlights: The study on 210 Po and 210 Pb in soil and mushrooms of genus Leccinum is presented. 210 Po and 210 Pb are important radiotoxic natural isotopes due to potential internal expose. The analyzed mushrooms are not hyperaccumulators in case of 210 Po and 210 Pb. The higher the bioconcentration factor (BCF) the lower the translocation factor (TF). Consumption of analyzed mushrooms is safe from radiological point of view.